PENINGKATAN HASIL BELAJAR MERODA MELALUI MODEL PEMBELAJARAN LANGSUNG - DWIYANTARI, ONENG (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract   For most students this phenomenon is only used as objects and not subjects. As a result, the material presented is not completely absorbed in the absence of feedback between the material provided by the teacher and received by the students, so the impact on learning outcomes of students who are not optimal. It is seen from the assessment that has been done, there are 19 students or 44.19% gain criterion of